Value of Education as Perceived by Mexican Immigrants and Caucasian American Citizens Employed in Agriculture in Louisiana - Richard Johnson; Joe Kotrlik (Journal of International Agricultural and Extension Education, 2012)
Agriculture operations benefit from the employment of Mexican immigrants through government programs that supply workers to the industry. Therefore, many crawfish farm operations in Louisiana employ both U.S. citizen and Mexican immigrant labor to operate efficiently. The purpose of this study was to compare selected characteristics of farm workers as well as to explore values related to education, as sorted by citizenship and ethnicity. The results of this study indicated significant differences in Mexican immigrant and Caucasian U.S. citizen crawfish farmers’ educational backgrounds and demographic characteristics, while finding that both groups held similar values about education. In general, the Mexican immigrant group was younger and had a lower overall educational attainment than the Caucasian U.S. citizens group. However, education was perceived as equally important by both groups. The results of this study can be used by extension services and other educational programs to direct future educational activities based on collected information related to educational values and perceptions of farm employees in Louisiana. These activities can enhance the value of educational programs that are meant to serve all populations.
Keywords: Education; Immigrants; Agriculture; Louisiana; Crawfish